Formations of the secular: christianity, islam, modernity - Asad, Talal (Cultural memory in the present, 2003)
Frontmatter -- Contents -- Acknowledgments -- Introduction: Thinking about Secularism -- 1 What Might an Anthropology of Secularism Look Like? -- 2 Thinking about Agency and Pain -- 3 Reflections on Cruelty and Torture -- 4 Redeeming the “Human” Through Human Rights -- 5 Muslims as a “Religious Minority” in Europe -- 6 Secularism, Nation-State, Religion -- 7 Reconfigurations of Law and Ethics in Colonial Egypt -- Index